2016
DOI: 10.1002/mnfr.201500789
|View full text |Cite
|
Sign up to set email alerts
|

Distinct physiological, plasma amino acid, and liver transcriptome responses to purified dietary beef, chicken, fish, and pork proteins in young rats

Abstract: To conclude, short-term feeding of different meat proteins resulted in distinct physiological and transcriptome changes in young rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 23 publications
(28 reference statements)
2
43
0
Order By: Relevance
“…Animal proteins, especially those from diets, seem to support better muscle protein synthesis than plant proteins 51 . The contents of leucine, isoleucine, phenylalanine + tyrosine, valine and lysine in soybean protein were significantly lower than those in these meat proteins 52 . The soy protein and casein diets for vegetarians showed no significant advantages for muscle health.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Animal proteins, especially those from diets, seem to support better muscle protein synthesis than plant proteins 51 . The contents of leucine, isoleucine, phenylalanine + tyrosine, valine and lysine in soybean protein were significantly lower than those in these meat proteins 52 . The soy protein and casein diets for vegetarians showed no significant advantages for muscle health.…”
Section: Discussionmentioning
confidence: 65%
“…As white meat, the fish and chicken protein groups showed similar results of oxidation and anti-oxitation in muscle because they had similar amino acid composition. And the chicken protein diet showed stable oxidative and anti-oxidative status from day 7 to day 14, which may be related the comprehensive and rich composition of amino acids according to amino acid score in previous publication 52 . However, beef protein was quite different from pork protein since they had different amino acid composition.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In vitro studies have suggested the beneficial properties of FPH-derived bioactive peptides, with potential applications for intestinal health [16,17], serum and liver cholesterol/lipid profile [18][19][20][21], fatty acid metabolism [22], postprandial glucose control [21], and hypertension [23]. There is also evidence in rodents that fish protein may increase plasma AA concentrations, their transport pathways [24], and associated fast-twitch muscle gene expression and mass [20]. Bioactive peptides released in the process of hydrolysation may also possess desirable immunomodulatory, anti-inflammatory, antioxidant, and neuroprotective effects [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%